A Proposed Control System for Checkmating an Aeronautics Agency Riddled with Fraud - Onwudebelu, Ugochukwu; Fasola, Olusanjo Olugbemi (Transactions on Engineering and Computing Sciences, 2018)
In recent year the nature of airports has changed vastly. Aviation problem is a chain and some time it trends is complex. It is a sector that changes with time and shared various challenges. Corruption is now the centre of gravity in most nations and it sucks every value, every moral and every drop of human compassion into its vortex. Fraud (be it procurement or maintenance frauds)in the aviation ministry in any country can only continue to make the aviation sector unsafe and thus exacerbate the increasing level of violation of the citizens’ human right to life and to security and dignity of the person. Consequently, the immediate future for airlines will be shaped by how well they cope with the current economic crisis. Imagine the following information scenario: the aviation industry is generating a lot of money in many countries of the world but the reverse is the case in our country, where USD 800 trillion was invested in aviation industry five years ago and this year the aviation industry is indebted of USD 200 billion with assets worth of USD 100 billion only. This will definitely cause such aviation industry to be weak and stagnant. In this paper, we look at the causes and then design a system for detecting and controlling the causes of these abnormalities. This becomes especially important since airports are unique in nature and what works at one may not be successful at another as the operating environment may not be comparable. Non-aviation revenue will be looked at as a key factor in generating revenue for this all important sector. In our research, we aim at checkmating and eliminating criminal activity against the aviation industry, people, customers, suppliers or other stakeholders (with a ‘zero tolerance’ strategy in relation to crime and corruption) as well as revenue generation. This system, if implemented will be able to manage and control crime, corruption, fraud as well as generate fund for the industry.